2009
DOI: 10.1002/uog.6284
|View full text |Cite
|
Sign up to set email alerts
|

Role of three‐dimensional power Doppler in the antenatal diagnosis of placenta accreta: comparison with gray‐scale and color Doppler techniques

Abstract: Objective To assess the role of three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 25 publications
5
140
1
8
Order By: Relevance
“…Based on our experience and the literature, it should be possible, especially for placenta increta or percreta [8,15,21] . The placental implantation site must be explored carefully, especially when the placental insertion is anterior and previa and the patient has undergone a previous cesarean delivery.…”
Section: Discussionmentioning
confidence: 96%
“…Based on our experience and the literature, it should be possible, especially for placenta increta or percreta [8,15,21] . The placental implantation site must be explored carefully, especially when the placental insertion is anterior and previa and the patient has undergone a previous cesarean delivery.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Shi et al (39) found that the most prominent grayscale sign to diagnose placenta accreta was dilated vessels extending from the placenta to the myometrium, and the most prominent color Doppler diagnostic sign was the presence of abnormal vessels connecting the placenta to the bladder. Shi et al (40) found that numerous vessels observed by the 3D power Doppler was the best single diagnostic sign of placenta accreta, with 97% sensitivity, and they concluded that the 3D power Doppler is a useful tool for the diagnosis of MAP. Chou et al (12) found that the (41) found that irregular tortuous vessels affecting the entire placenta and the uterine serosa-bladder interface were the diagnostic signs of MAP observed by the 3D power Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…Shih et al [3] have reported that three-dimensional power Doppler signs had a sensitivity of 100 % and a specificity of 85 % when at least one of the three criteria was present, i.e., confluent vessels between bladder and uterine serosa, hypervascularity on lateral view and inseparable cotyledonal and intervillous circulations with chaotic appearance.…”
Section: Discussionmentioning
confidence: 99%